Highly targeted cholera vaccination campaigns in urban setting are feasible: The experience in Kalemie, Democratic Republic of Congo - Massing, Louis Albert; Aboubakar, Soumah; Blake, Alexandre; Page, Anne-Laure; Cohuet, Sandra; Ngandwe, Adalbert; Mukomena Sompwe, Eric; Ramazani, Romain; Allheimen, Marcela; Levaillant, Philippe; Lechevalier, Pauline; Kashimi, Marie; et al. (PLOS Neglected Tropical Diseases, 2018)
Author summary The oral cholera vaccine, Shanchol, has already been shown as an effective tool in controlling a cholera outbreak. The limited amount of doses, concurrently with the logistic constraints associated with a targeted vaccination campaign are serious difficulties to tackle in order to organize a vaccination campaign in an urban setting. Although the World Health Organization recommends its use for cholera control in endemic countries, the fact remains that the use of the oral cholera vaccine in endemic setting has scarcely been described, especially in an urban setting, until now. Médecins Sans Frontières and the Ministry of Health from Democratic Republic of Congo organized a vaccination campaign of a limited part of the urbanized and highly endemic city of Kalemie, in the Tanganyika Province using a door to door strategy. The vaccine coverage in the targeted zones was high and demonstrated the feasibility of cholera vaccination campaign in this setting but also the need for creative strategies in order to reach population remaining hard to vaccine.